Epinephrine Production in Th17 Cells and Experimental Autoimmune Encephalitis - Yang, Pinguang; Tian, Hong; Zou, Yong-Rui; Chambon, Pierre; Ichinose, Hiroshi; Honig, Gerard; Diamond, Betty; Kim, Sun Jung (Frontiers in Immunology, 2021)
Epinephrine is a hormone secreted primarily by medullary cells of the adrenal glands which regulates permeability of blood-brain barrier (BBB). Recent studies showed signaling by epinephrine/epinephrine receptor in T cells is involved in autoimmune diseases. Nevertheless, the production of epinephrine by T cells and its pathogenic function in T cells are not well investigated. Our results show that phenylethanol N-methyltransferase (PNMT), a rate-limiting enzyme of epinephrine synthesis, is specifically expressed in vitro in differentiated TH17 cells and in tissue-resident TH17 cells. The induction of PNMT was not observed in other effector T cell subsets or regulatory T cells. Epinephrine producing TH17 cells do not secrete GM-CSF or express surface IL7Ra. To delineate the function of epinephrine-production in TH17 cells, we generated a TH17-specific knockout of tyrosine hydroxylase (Th) by breeding a Th-flox and a ROR-gt-CRE mouse (Th-CKO). Th-CKO mice are developmentally normal with an equivalent T lymphocyte number in peripheral lymphoid organs. Th-CKO mice also show an equivalent number of TH17 cells in vivo and following in vitro differentiation. To test whether epinephrine-producing TH17 cells are key for breaching the BBB, migration of T cells through mouse brain endothelial cells was investigated in vitro. Both epi+ wild-type and epi- Th17 cells migrate through an endothelial cell barrier. Mice were immunized with MOG peptide to induce experimental autoimmune encephalitis (EAE) and disease progression was monitored. Although there is a reduced infiltration of CD4+ T cells in Th-CKO mice, no difference in clinical score was observed between Th-CKO and wild-type control mice. Increased neutrophils were observed in the central nervous system of Th-CKO mice, suggesting an alternative pathway to EAE progression in the absence of TH17 derived epinephrine.